Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Matematika Materi Operasi Bilangan Bulat Pada Siswa Kelas V SD Negeri 2 Cisandawut Tahun Ajaran 2018/2019 - Ernawati, Ernawati; Dewi, Dara Kartika; Nurhayati, Leni; Agina, Selvia; Khodijah, Siti Sarah; Fitriani, Nelly (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2020)
This descriptive research aims to analyze the errors of students in completing integer operations in fifth grade students at SD Negeri 2 Cisandawut Sindangkerta District, West Bandung Regency. The subjects in this study were all fifth grade students of SD Negeri 2 Cisandawut with a total of 36 people. Data collection methods used in this study were tests, interviews and documentation. Data analysis techniques in this study used quantitative descriptive analysis and qualitative descriptive analysis. Based on the results of data analysis and discussion, fifth grade students at SD Negeri 2 Cisandawut have low ability to understand integer operation material. This is indicated by the average percentage of achievement of all students which is only 12% with a very low category. The indicator of the problem with the lowest percentage of achievement is performing mixed integer operations. From the results of working on questions 1, 2, 3, 4, or question 5, the type of process skill error is the biggest type of error made by the subject even though the numbers are different. Process skill errors made by the subjects in working on questions 1, 2, 3, 4 and 5 tend to have the same type of error that is the subject is not able to do because they do not know the procedures or steps that will be used to solve the problem correctly